Commercial applications of company law in Malaysia, 3rd. ed. - Mohd. Sulaiman, Aiman @ Nariman; Bidin, Aishah; Hanrahan, Pamela; Ramsey, Ian; Stapledon, Geof (Commerce Clearing House Sdn Bhd (Wolters Kluwer), 2008)
Commercial Applications of Company Law in Malaysia (Professional) is a comprehensive company law reference guide which takes into consideration the unique requirements of students, lecturers and professionals in area of law. This practical reference focuses on ordinary events and issues faced by companies, and explain and applies the law in a concise and accessible manner. This book also introduces a unique teaching method which has been well received in Australia and is reflecting the latest companies (Amendment) Act 2007.